Elliptically bent conformal phased array of modified box-horns for hyperthermia treatment of tumors - Gupta, R.C.; Singh, S.P. (My University, 2007)
A novel and effective hyperthermia applicator utilizing an elliptically bent conformal phased array of modified box-horns is analyzed using Fresnel-Kirchhoff scalar diffraction field theory. This configuration is mainly intended as a specialized and very effective applicator for hyperthermia treatment of tumor within curved portions of human body such as abdomen, chest, neck, etc. It is proposed that the interior of the modified box-horn as well as feeding device be filled with de-ionized water to provide a better impedance match to the tissue. The contour distribution of specific absorption rate (SAR) in x-y plane, SAR distribution in z-direction, penetration depth, power absorption coefficient and effective field size (EFS) due to the conformal array as well as single modified box-horn are evaluated and compared at 2450 MHz. The effect of change in phase and amplitude excitation of modified box-horn of the array on SAR distribution is also investigated. Results demonstrate that conformal phased array of modified box-horns offers marked improvement in SAR distribution and penetration depth over single modified box-horn. The results obtained by the present analysis for linear array of four titanium dioxide loaded horns terminated in water are validated against published experimental results available in the literature.
Keywords: Absorption; Magnetic field effects; Amplitude excitation; Conformal arrays; SAR distribution; Synthetic apertures